Comparison of serological test for toxoplasmosis using Immunostick Assay, ELISA and Latex Agglutination Test - Subekti, Didik T.; Kusumaningtyas, E. (Indonesian Journal of Animal and Veterinary Sciences, 2011)
Many serological methods were developed in order to improve detection and identification of an infectious diseases. ELISA (enzyme linked immunosorbent assay), is a well-known as the most serological technique and widely used for infectious disease diagnoses, especialy toxoplasmosis in human and animal. Unfortunately, the technique requires specific tools and expertise that are not always available in the field. Inn addition, ELISA needs longer process than other techniques for both small and large number of samples. Another serological assay, namely Latex Agglutination Test (LAT) was known as populer and mostly applied in field for toxoplasmosis diagnosis in Indonesia, both for human and animal serum. However, the accuracy of this technique was slightly lower compared to ELISA, especially for weakly seropositive. Recently, an immunostick assay technique was developed as alternative serological method which has high accuracy as ELISA. The immunostick assay was rapid and simple like latex agglutination test. The immunostick assay was evaluated to detect Toxoplasma gondii infection in goat serum samples and compared to ELISA and LAT. The immunostick assay had a true agreement 95.88% - 100% againts ELISA and their strength of agreement was very good aggreement with ELISA (k = 0.796; AC1 = 0.948). However, LAT had true agreement only 75.74%, either with ELISA or immunostick assay. The strength of agreement of LAT was moderately aggreement with ELISA or immunostick assay (k = 0.447; AC1 = 0.582). Therefore, the immunostick assay could become the first choice for rapid serological assay on toxoplasmosis diagnosis, both in the laboratory and in the field. Key Words: Latex Agglutination, ELISA, Immunostick Assay, FELISA, Toxoplasmosis